Synergizing Advocacy and Communication: A Strategic Model for Sustainable Development in Non-Governmental Organizations - April, Aprilia Natasya; Donna, Donna Ardila Aprillia; Maulana, Muhamad Maulana; Ruslan, Ruslan (Pencerah, 2024)
This study examines the effectiveness of advocacy and communication strategies employed by the Bojonegoro Institute in Bojonegoro and WALHI in Bangka Belitung, focusing on their impact across social, economic, environmental, and political dimensions. Advocacy and communication are pivotal, interdependent components in addressing environmental and social issues caused by institutional or corporate operations. The research adopts a descriptive qualitative methodology, utilizing in-depth, unstructured interviews with purposive sampling to identify key informants. The findings reveal that advocacy and communication significantly contribute to the existence and success of non-governmental organizations (NGOs). The Bojonegoro Institute’s advocacy promotes equitable and sustainable governance in the oil and gas sector, while WALHI in Bangka Belitung pushes for environmental crisis mitigation through governmental policy interventions. Socially, both organizations enhance public awareness of environmental and social issues. Economically, the Bojonegoro Institute boosts local productivity, investment appeal, and income levels, whereas WALHI’s initiatives enhance tourism, agricultural production, and economic resilience. Environmentally, these organizations strengthen conservation efforts and public environmental consciousness. Politically, their strategic advocacy facilitates policy-making for regional sustainability. In conclusion, effective advocacy and communication strategies enable NGOs to achieve their objectives and provide substantial positive impacts across multiple aspects of regional development. The synergy of these strategies reinforces their pivotal role in fostering societal well-being and environmental stewardship